Optimizing Expectations via Mobile Apps: A New Approach for Examining and Enhancing Placebo Effects - Gruszka, Piotr; Burger, Christoph; Jensen, Mark P. (Frontiers in Psychiatry, 2019)
There is growing interest in interventions that enhance placebo responses in clinical practice, given the possibility that this would lead to better patient health and more effective therapy outcomes. Previous studies suggest that placebo effects can be maximized by optimizing patients’ outcome expectations. However, expectancy interventions are difficult to validate because of methodological challenges, such as reliable blinding of the clinician providing the intervention. Here we propose a novel approach using mobile apps that can provide highly standardized expectancy interventions in a blinded manner, while at the same time assessing data in everyday life using experience sampling methodology (e.g., symptom severity, expectations) and data from smartphone sensors. Methodological advantages include: (1) full standardization, (2) reliable blinding and randomization, (3) disentangling expectation effects from other factors associated with face-to-face interventions, (4) assessing short-term (days), long-term (months) and cumulative effects of expectancy interventions, and (5) investigating possible mechanisms of change. Randomization and expectancy interventions can be realized by the app (e.g., after the clinic/lab visit). As a result, studies can be blinded without the possibility for the clinician to influence study outcomes. Possible app-based expectancy interventions include, for example, verbal suggestions and imagery exercises, although a large number of possible interventions (e.g., hypnosis) could be evaluated using this innovative approach.